European Society of Gynaecological Oncology Guidelines for the Management of Patients with Vulvar Cancer - Update 2023 - Oonk, Maaike H M; Planchamp, François; Baldwin, Peter; Mahner, Sven; Mirza, Mansoor Raza; Fischerová, Daniela; Creutzberg, Carien L; Guillot, Eugénie; Garganese, Giorgia; Lax, Sigurd; Redondo, Andres; Sturdza, Alina; et al. (International journal of gynecological cancer, 2023)
BACKGROUND: As part of its mission to improve the quality of care for women with gynecological cancers across Europe, the European Society of Gynaecological Oncology (ESGO) first published in 2017 evidence-based guidelines for the management of patients with vulvar cancer. OBJECTIVE: To update the ESGO guidelines based on the new evidence addressing the management of vulvar cancer and to cover new topics in order to provide comprehensive guidelines on all relevant issues of diagnosis and treatment of vulvar cancer. METHODS: The ESGO Council nominated an international development group comprised of practicing clinicians who provide care to vulvar cancer patients and have demonstrated leadership through their expertize in clinical care and research, national and international engagement and profile as well as dedication to the topics addressed to serve on the expert panel (18 experts across Europe). To ensure that the statements were evidence-based, new data identified from a systematic search were reviewed and critically appraised. In the absence of any clear scientific evidence, judgment was based on the professional experience and consensus of the international development group. Prior to publication, the guidelines were reviewed by 206 international practitioners in cancer care delivery and patient representatives. RESULTS: The updated guidelines cover comprehensively diagnosis and referral, staging, pathology, pre-operative investigations, surgical management (local treatment, groin treatment, sentinel lymph node procedure, reconstructive surgery), (chemo)radiotherapy, systemic treatment, treatment of recurrent disease (vulvar, inguinal, pelvic, and distant recurrences), and follow-up. Management algorithms are also defined.
Keywords: gynekologie; Female; Vulvar Neoplasms; Gynecology; lidé; nádory vulvy; Humans; ženské pohlaví; Plastic Surgery Procedures; Europe; Evropa; zákroky plastické chirurgie